2014
DOI: 10.1021/jf4048435
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Resveratrol Derivatives in Humans after Oral Administration of Melinjo (Gnetum gnemon L.) Seed Extract Powder

Abstract: Fruits and seeds of melinjo (Gnetum gnemon L.) are resveratrol derivative-rich materials. Pharmacokinetics of resveratrol derivatives in healthy volunteers after oral administration of 1000 mg of melinjo seed extract (MSE) powder were assessed and compared with those after oral dosing of trans-resveratrol (tRV) powder containing 4.8 mg of tRV only, equivalent to the content in 1000 mg MSE powder. Plasma tRV concentrations with enzymatic hydrolysis were maintained over 24 h, with a tmax of 12 h and a mean resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…Hence, significant attention has been given to the derivatives of resveratrol to overcome these drawbacks. For example, a recent study on the pharmacokinetics of gnetin C, a resveratrol dimer, showed increased bioavailability when orally consumed compared with resveratrol (38). Since the oligostilbenes in the present study showed improved potency in cancer chemoprevention compared with resveratrol, further investigation of their bioavailability is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…Hence, significant attention has been given to the derivatives of resveratrol to overcome these drawbacks. For example, a recent study on the pharmacokinetics of gnetin C, a resveratrol dimer, showed increased bioavailability when orally consumed compared with resveratrol (38). Since the oligostilbenes in the present study showed improved potency in cancer chemoprevention compared with resveratrol, further investigation of their bioavailability is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study reported that it reduced tumor cell proliferation by 5% in patients with colorectal cancer 49) . In contrast, few studies have examined MSE, with only two demonstrating its safety 29, 50) .…”
Section: Discussionmentioning
confidence: 99%
“…Common stilbenoids which are contained in the seeds of Gnetum gnemon are gnetin C, GC, GL, gnemoside A, GMA, GMC, GMD [2] and trans-resveratrol [6]. Among these stilbenoids, resveratrol is a compound that was found in 1940 to have wide biological activities.…”
Section: Introductionmentioning
confidence: 99%